Vera Wong's guide to snooping (on a dead man) - Sutanto, Jesse Q. (A Vera Wong novel, 2025)
"Vera Wong is back and as meddling as ever in this follow-up to the hit Vera Wong's Unsolicited Advice for Murderers.... Ever since a man was found dead in Vera's teahouse, life has been good. For Vera, that is. She's surrounded by loved ones, her shop is bustling, and best of all, her son, Tilly, has a girlfriend! All thanks to Vera, because Tilly's girlfriend is none other than Officer Selena Gray. The very same Officer Gray she had harassed while investigating the teahouse murder. Still, Vera wishes more dead bodies would pop up in her shop, but one mustn't be ungrateful, even if one is slightly . . . bored. Then Vera comes across a distressed young woman who is obviously in need of her kindly guidance. The young woman is looking for a missing friend. Fortunately, while cat-sitting at Tilly and Selena's, Vera finds a treasure trove: Selena's briefcase. Inside is a file about the death of an enigmatic influencer-who also happens to be the friend that the young woman was looking for. Online, Xander had it all: a parade of private jets, fabulous parties with socialites, and a burgeoning career as a social media influencer. The only problem is, after his body is fished out of the water at Mile Rock Beach, the police can't seem to actually identify him. Who was Xander Lin? Nobody knows. Every contact is a dead end. Everybody claims not to have known him, even his parents. Vera is determined to solve Xander's murder. After all, doing so would surely be a big favor to Selena, and there is nothing she wouldn't do for her future daughter-in-law"--